Colaboración y sanción corporativa: whistleblowing, investigaciones internas y el dilema de la prueba ilícita - Goena Vives, Beatriz (2025)
The article analyzes corporate cooperation within the framework of corporate criminal liability, highlighting its role as an instrument of reactive prevention rather than as a retributive sanction. It studies the comparative evolution of different legal systems —United States, countries of the Germanic tradition, Europe, and Ibero-America— regarding the incentives for companies to cooperate with the authorities through confession, reparation, improvement of compliance, and internal investigations. Special attention is given to the problems raised by cooperation when it relies on evidence obtained illegally, both by internal whistleblowers and in the context of corporate investigations. The paper examines the tension between encouraging cooperation and respecting fundamental rights, proposing clear limits: cooperation should not be the sole criterion for exemption from liability, and information obtained in violation of guarantees cannot justify procedural benefits.